Construction safety questions and answers a practical approach - Perry, Pat, 1954- (Thomas Telford, 2003)
Aimed at those responsible for construction site safety, this volume follows a question and answer format. It covers new legislation whilst referring to HSE guidance notes and approved codes of practice. Comprehensive in content, everything is covered from fire safety to handling hazardous chemicals.
Keywords: Construction industry -- Safety measures.; elektronické knihy; electronic books